DEVELOPMENT OF SELF HELP BOOK ON MINDFULNESS TECHNIQUES IN OVERCOMING ACADEMIC STRESS OF FINAL YEAR STUDENTS - Mirnawati, Mirnawati; Afiati, Evi; Rahmawati, Rahmawati (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2024)
Stress is a common problem among students, especially in academic environments. Academic stress refers to feelings of pressure experienced by pupils or students which are characterized by various physical and emotional reactions due to academic demands from lecturers, teachers, parents, and the need to complete assignments on time. This research aims to produce self-help book learning media on how to overcome academic stress using mindfulness techniques aimed at final year students at the Faculty of Education and Teacher Training at a university. The research method used is a research and development (R&D) method. The research and development of this self-help book uses ADDIE, which is an extension of analysis, design, development, implementation and evaluation (analyze, implementation, evaluate, design & development). Evaluation is carried out by media and material expert validators, language experts and practitioner experts. Based on these data, the evaluation results show that the validity of media and material experts is 78.3% (feasible), the validity of language experts is 89.3% (very feasible), and the validity of practitioner experts is 82.7% (decent) and students are 90.3% (very feasible). worthy) means that this self-help book is suitable for use.